2014
DOI: 10.4161/onci.27185
|View full text |Cite
|
Sign up to set email alerts
|

Combining NK cells and mAb9.2.27 to combat NG2-dependent and anti-inflammatory signals in glioblastoma

Abstract: Glioblastoma is a deadly brain cancer with limited treatment options. Targeting chondroitin sulfate proteoglycan 4 (CSPG4, best known as NG2) with the monoclonal antibody mAb9.2.27 and activated natural killer (NK) cells abrogated the tumor growth and prolonged the survival of glioblastoma-bearing animals by favoring the establishment of a pro-inflammatory microenvironment. The combination of NK cells and mAb9.2.27 recruited ED1+CCR2low macrophages that stimulated ED1+ED2lowMHCIIhigh microglial cells to exert … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 10 publications
0
27
0
Order By: Relevance
“…Having previously shown that NK cells are involved in mediating the effect of EE on glioma progression ( Garofalo et al, 2015 ), we now investigated the role of NK cells in EE-induced phenotypic switch of myeloid cells. Other studies also have correlated microglia/macrophage activation state with NK cell activity ( Kmiecik et al, 2014 ). We demonstrate that NK cell depletion completely abolishes the effect of EE on pro- and anti-inflammatory gene expression in CD11b + cells.…”
Section: Discussionmentioning
confidence: 99%
“…Having previously shown that NK cells are involved in mediating the effect of EE on glioma progression ( Garofalo et al, 2015 ), we now investigated the role of NK cells in EE-induced phenotypic switch of myeloid cells. Other studies also have correlated microglia/macrophage activation state with NK cell activity ( Kmiecik et al, 2014 ). We demonstrate that NK cell depletion completely abolishes the effect of EE on pro- and anti-inflammatory gene expression in CD11b + cells.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting NG2/CSPG4 with mAb 9.2.27 and activated natural killer cells inhibited the tumor growth and improved the survival of GB-bearing animals with the establishment of a pro-inflammatory microenvironment [ 110 , 111 ]. Similar effects were obtained by miR-129-2 [ 34 ].…”
Section: Ng2/cspg4 In the Treatment Of Gliomasmentioning
confidence: 99%
“…We showed that combination treatment of adoptively transferred NK cells with mAb9.2.27 against NG2/CSPG4 in preclinical models of GBM induced synergistic therapeutic effects through TNF-α, a IFN-γ release, diminished IL-10, IL-6, and IL-1α. Combination NK cells + mAb9.2.27 induced potent ADCC mediated by Fcγ-IIR on microglia/macrophages that resulted in prolonged survival ( 158 , 159 ). mAb9.2.27 could not induce ADCC by NK cells proper , likely because of its IgG2a isotype, known to engage weakly the Fcγ-RIII on NK cells.…”
Section: Antibody-dependent Cellular Cytotoxicitymentioning
confidence: 99%